FIRST TITHONIAN RECORD OF PERFORATED PEDIASTRUM MEYEN S.L. SPECIES WITHIN EARLY–DIAGENETIC CARBONATE CONCRETIONS FROM THE VACA MUERTA FORMATION, NEUQUÉN BASIN, ARGENTINA. IMPLICATIONS FOR THE PALYNOLOGICAL ANALYSIS OF FINE-GRAINED ROCKS - Daniela Elizabeth Olivera; Marcelo Adrián Martínez; Germán Otharán; Luis Sebastián Agüero; Carlos Zavala (Publicación Electrónica de la Asociación Paleontológica Argentina, 2023)
The perforated Pediastrum Meyen s.l. species are recorded for the first time in the basal levels of the Tithonian Vaca Muerta Formation, extending its first stratigraphical record to ages as old as Late Jurassic times. Based on the ecological requirements of Pediastrum simplex var. clathratum and P. simplex var. biwaense, the previously warm paleoclimatic conditions suggested by the Late Jurassic of Neuquén Basin, are reinforced. The co-occurrence of the different mechanisms that interacted during the transport, accumulation, and early diagenesis of these sediments and their organic content would have allowed for the excellent preservation of the Pediastrum Meyen s.l. species.